EFFECTS OF SELECTED HERBICIDES ON SOIL BENEFICIAL BACTERIA AND DEHYDROGENASE ACTIVITY - Faith, Toluwani Samuel; Adeoyo, Olusegun Richard; Adesina, Abiola Olanike; Bello, Marcus Oluyemi; Adegbehingbe, Kehinde Tope; Adejumo, Timothy Olubisi (FUDMA Journal of Sciences, 2025)
Herbicides are weeds control agents but their misuse can negatively affect soil beneficial microorganisms and dehydrogenase activity. This study evaluated the effects of herbicides on soil bacterial populations and dehydrogenase activity (DHA). Glyphosate, isopropylamine, paraquat dichloride, atrazine, and dimethylamine salt were employed. An 8000 g composite soil sample was collected using soil a soil auger from 10 different points on the botanical farm of Adekunle Ajasin University, Akungba-Akoko with no herbicide application for at least five years. The physicochemical properties of the soil were determined using standard methods. Each 500 g soil sample was treated weekly with varying herbicide concentrations [manufacturer’s specification (X): ½X, X or 2X] for 21 days. Bacteria were isolated and identified using cultural, morphological, and biochemical characterization techniques. DHA was measured using a spectrophotometric assay and all data were subjected to analysis of variance (ANOVA). The findings revealed that untreated soil had the highest bacterial counts (14.67x106±0.882 CFU/mL), while glyphosate, isopropylamine, paraquat dichloride, atrazine, and dimethylamine salt exhibited significant reductions to 4.33x106±0.333, 3.67x106±0.333, 4.33x106±0.333, 3.67x106±0.667, and 4.33x106±0.333, respectively after 21 days of treatment. Similarly, glyphosate, isopropylamine, paraquat dichloride, atrazine, and dimethylamine salt reduced soil DHA to 11.02, 13.66, 22.94, 17.78, and 9.30 µg TPFg-1h-1, respectively compared to untreated soil (31.75 µg TPFg-1h-1). The results contribute to a broader understanding of herbicide-soil interactions and highlight how herbicide misuse can negatively affect soil health. Therefore, farmers are encouraged to always follow manufacturer’s specification, avoid prolong herbicides usage, and adopt practices that promote overall soil health.
Keywords: Dehydrogenase activity; Herbicides; Plant growth-promoting traits; Soil bacteria